Graphene Oxides as Epsilon-Near-Zero Platforms Operating in Terahertz Frequency Range - Jun, Seung Won; Yim, Jong Hyuk; Park, Ji Yong; Lee, Soonil; Ahn, Yeong Hwan (Laser and Photonics Reviews, 2024)
Epsilon-near-zero (ENZ) materials, with their unique light manipulation capabilities, have fascinating applications such as cloaking, super-resolution imaging, energy harvesting, and sensing. Herein, free-standing graphene oxide films are fabricated whose dielectric constant can be engineered by thermal reduction, resulting in ENZ characteristics at the transition between insulating and metallic phases. The ENZ frequency is found to be 0.4–0.5 THz under an annealing temperature of 200 °C, whereas another ENZ phase appeared at 360 °C. ENZ film can be transferred to curved metal surfaces, serving as superabsorbers that suppress wave reflection from underneath metal surfaces. Hyper-resolution in nondestructive THz imaging is also possible, owing to superior beaming. Spatial resolution is improved two-fold by adding the ENZ film, even when the metal pattern is enclosed by a paint layer. Lastly, hybrid sensors are developed by incorporating the meta-pattern on the free-standing ENZ substrate. The energy splitting of metamaterial resonance originating from the coupling with ENZ mode is observed. Hybridized devices have proven effective in detecting microorganisms with a low refractive index, owing to the unique dielectric configuration offered by ENZ material. Using the novel ENZ platform, a 15-fold improvement in microbial sensitivity is achieved compared with the conventional sensors.
Keywords: Epsilon-near zeros; Free standings; Graphene oxide films; Graphene oxides; Hyper-resolution; Metal surfaces; Super resolution imaging; Super-absorber; Tera Hertz; Terahertz frequency range; epsilon-near-zero; graphene oxide; hyper-resolution; super-absorber; terahertz